Effects of thermal annealing on the optical, spectroscopic, and structural properties of tris (8-hydroxyquinolinate) gallium films grown on quartz substrates - Muhammad, F.F.; Sulaiman, K. (Elsevier, 2011)
In this study we report the optical, spectroscopic, and structural properties of vacuum deposited tris (8-hydroxyquinolinate) gallium film upon thermal annealing in the temperature range from 85 degrees C to 255 degrees C under a flowing nitrogen gas for 10 min. The optical UV-vis-NIR and luminescence spectroscopy measurements were performed to estimate the absorption bands, optical energy gap (E(g)), and photoluminescence (PL) of the films. Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) techniques were used to probe the spectroscopic and structural nature of the films. We show that, by annealing the films from 85 degrees C to 235 degrees C, it is possible to achieve an enhanced absorption and increased photoluminescence to five times stronger than that of the pristine film. The PL quenching at 255 degrees C was attributed to the presence of plainer chains allow easy going for excitons to a long distance due to the crystalline region formation of alpha-Gaq3 polymorph. The reduction in E(g) and infrared absorption bands upon annealing were referred to the enhancement in pi-pi interchain interaction and conformational changes by re-arrangement of the Gaq3 quinolinate ligands, respectively. Stokes shift for the films were observed and calculated. From the differential scanning calorimetry, DSC measurements, higher glass transition temperature was observed for Gaq3 (T(g) = 182 degrees C) compared to that of Alq3 (T(g) = 173 degrees C), which suggests the existence of stronger dipolar interaction in Gaq3 due to the Ga(3+) cation effect, in comparison to that of A1q3. (C) 2011 Elsevier B.V. All rights reserved.